Antibacterial Activities of Echinops kebericho Mesfin Tuber Extracts and Isolation of the Most Active Compound, Dehydrocostus Lactone - Deyno, Serawit; Mtewa, Andrew G.; Hope, Derick; Bazira, Joel; Makonnen, Eyasu; Alele, Paul E. (Frontiers in Pharmacology, 2021)
Echinops kebericho Mesfin is traditionally used for the treatment of various infectious diseases. This study investigated antibacterial activity of the essential oil (EO) and the different fractions of ethanol extract. The most active component was isolated and identified. Isolation and purification was accomplished using chromatographic techniques while identification was done by spectroscopic method. Minimum inhibitory concentration (MIC) was determined using the broth micro-dilution method. In bioactive-guided isolation, percent inhibition was determined using optical density (OD) measurement. The MICs of the essential oil ranged from 78.125 µg/ml to 625 µg/ml, and its activity was observed against methicillin-resistant S. aureus (MRSA, NCTC 12493). Ethyl acetate fraction showed high activity against MRSA (NCTC 12493), MIC = 39.075 µg/ml followed by E. faecalis (ATCC 49532), MIC = 78.125 µg/ml and was least active against K. pneumonia (ATCC 700603), MIC = 1250 µg/ml. MIC of hexane fraction ranged from 156.2- µg/ml to E. faecalis (ATCC 49532) to 1250 µg/ml to E. coli (NCTC 11954). The MICs of chloroform fraction ranged from 312.5 to 2500µg/ml; while butanol fraction could be considered pharmacologically inactive as its MIC value was 2500 µg/ml for all and no activity against E. coli (NCTC 11954). Dehydrocostus lactone was successfully isolated and identified whose MIC was 19.53 μg/ml against MRSA. Dehydrocostus lactone isolated from E. kebericho M. showed noteworthy antibacterial activity which lends support to ethnopharmacological use of the plant. Further optimization should be done to improve its antibacterial activities and pharmacokinetic profile.